Minor triterpenes from an aqueous extract of the hook-bearing stem of Uncaria rhynchophylla. Issue 4 (3rd April 2021) - Li, Ruo-Fei; Guo, Qing-Lan; Zhu, Cheng-Gen; Xu, Cheng-Bo; Wei, Ya-Zi; Cai, Jian; Wang, Yue; Sun, Hua; Zhang, Tian-Tai; Shi, Jian-Gong
Abstract: Six new triterpenes, uncarinic acids KP (1–6 ), along with 24 known analogues, were isolated as minor constituents of an aqueous decoction of the hook-bearing stems of Uncaria rhynchophylla (Gou-teng). By comprehensive spectroscopic data analysis, their structures were elucidated as derivatives of olean-12-en-28-oic acid and urs-12-en-28-oic acid with different oxidized forms at C-3, C-6, and/or C-23, respectively. Cell-based preliminary bioassay showed that the ( E )-/( Z )-coumaroyloxy and ( E )-/( Z )-feruloyloxy units at C-27 of olean-12-en-28-oic acid and urs-12-en-28-oic acid played roles in their bioactivities.